The Effect of Using Visual Interactive Worksheet-Based Language Acquisition Design on Early Childhood Language Acquisition - Akhmad Zamroni; Pamela Maher Wijaya (INCARE, International Journal of Educational Resources, 2026)
This study aimed to find the effect of using visual interactive worksheet-based language acquisition design on the development of early childhood English vocabulary acquisition because language development in early childhood is essential for building basic communication skills in a child's second language, and  how the use of interactive and engaging worksheets can improve vocabulary, word meaning, and comprehension. This study used mix-method to collect and analysis the data. This study was conducted at the PIAUD (Islamic Education for Early Childhood) Laboratory of STIT Ihsanul Fikri Pabelan; 20 children aged 3-6 years participated in the study. Pre-test and post-test assessments were used to measure language skills, while teacher observation and interview data provided additional insight. Results showed a good improvement in children's vocabulary recognition (from 58% to 84%), meaning of new vocabulary (from 43% to 70%), and comprehension (from 60% to 75%) after using this method. The findings highlight the effectiveness of worksheets that incorporate well aids, interactive tasks, and age-appropriate activities for early childhood development. In addition, this study emphasis the importance of teacher training in utilizing these resources effectively and advocates the integration of structured English materials into educational standards. The results show that visual-designed worksheets are a valuable tool in early childhood language development, with implications for improving language learning practices globally.